Label‐Free Proteomic Analysis of Wheat Gluten Proteins and Their Immunoreactivity to ELISA Antibodies. Issue 5 (27th February 2017) - Martínez‐Esteso, María José; Brohée, Marcel; Nørgaard, Jørgen; O'Connor, Gavin
Abstract : Enzyme‐linked immunosorbent assay (ELISA) methods are currently the most widely used for gluten quantification. However, the lack of comparable measurements among commercial kits has caused much concern. Here, we studied the immunoreactivity of five commercial ELISA kits to wheat gluten fractionated by reversed‐phase high‐performance liquid chromatography and identified the proteins and peptides in the resulting fractions by mass spectrometry to understand the extent to which these may be contributing to the lack of comparability. The investigated monoclonal antibodies clearly demonstrated divergent responses to the fractioned wheat gluten proteins and sometimes to their initial intended targets. To make comparable gluten measurements a reality, the analytical measurement community requires a set of agreed peptide markers, known conversion factors from these markers to total gluten content, and appropriately characterized (certified) reference materials representative of gluten.